Mitochondrial DNA disorders in neuromuscular diseases in diverse populations - Fei Gao; Katherine R Schon; Jana Vandrovcova; Özlem Yayıcı Köken; Sharika Raga; Kireshnee Naidu; Maryke Schoonen; Nimita Rani; Pedro Tomaselli; Dipti Baskar; Musambo Kapapa; Ipek Polat; et al. (Annals of Clinical and Translational Neurology)
Abstract Neuromuscular features are common in mitochondrial DNA (mtDNA) disorders. The genetic architecture of mtDNA disorders in diverse populations is poorly understood. We analysed mtDNA variants from whole‐exome sequencing data in neuromuscular patients from South Africa, Brazil, India, Turkey and Zambia. In 998 individuals, there were two definite diagnoses, two possible diagnoses and eight secondary findings. Surprisingly, common pathogenic mtDNA variants found in people of European ancestry were very rare. Whole‐exome or ‐genome sequencing from undiagnosed patients with neuromuscular symptoms should be re‐analysed for mtDNA variants, but the landscape of pathogenic mtDNA variants differs around the world.